Los aeropuertos (Ediciones Castillo [u.a.], 2014)
A lone traveler arrives at the airport at dawn. The city is just a stopover on route to another place; man must wait all day before his next flight, and decides to take a walk for entertainment. After visiting various places, visit an animal shelter where he meets Lost, a dog homeless. Together through the city and playing in the park until the time to leave the man arrives; Fortunately, the game has changed both: the traveler takes flight with the satisfaction of having found a friend, and Lost is adopted by a girl who witnessed his wanderings around the city